2012
DOI: 10.1007/s00125-012-2799-3
|View full text |Cite
|
Sign up to set email alerts
|

Amylin-induced downregulation of hippocampal neurogenesis is attenuated by leptin in a STAT3/AMPK/ERK-dependent manner in mice

Abstract: Aims/hypothesis Both leptin and insulin sensitivity have been linked with pathophysiological processes involving the central nervous system in general, and the hippocampus in particular, but the role of leptin in hippocampal neurogenesis has not yet been elucidated. Also, no previous studies have evaluated whether amylin or the endogenous insulin sensitiser adiponectin interact with leptin to alter hippocampal neurogenesis in mouse hippocampal neuronal (HN) cells or investigated the role of leptin, amylin or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Importantly, recent in vitro evidence has suggested that amylin activates signal transducer and activator of transcription 3 (STAT3), AMPK, and ERK signalling pathways in an additive fashion in hippocampal cells. Furthermore, amylin has been shown to decrease cell proliferation in a concentration‐dependent manner, although this effect is diminished following leptin administration and is dependent on STAT3/AMPK/ERK signalling . Because ERK is a significant downstream target mediating the physiological effects of amylin in pancreatic beta cells, amylin may also have beneficial effects on human physiology and pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent in vitro evidence has suggested that amylin activates signal transducer and activator of transcription 3 (STAT3), AMPK, and ERK signalling pathways in an additive fashion in hippocampal cells. Furthermore, amylin has been shown to decrease cell proliferation in a concentration‐dependent manner, although this effect is diminished following leptin administration and is dependent on STAT3/AMPK/ERK signalling . Because ERK is a significant downstream target mediating the physiological effects of amylin in pancreatic beta cells, amylin may also have beneficial effects on human physiology and pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that STAT3/AMPK/ERK signaling is important for the maintenance of hippocampal development, which demonstrates that hippocampal neurogenesis, i.e., neurite outgrowth, and synaptogenesis are activated through STAT3/AMPK/ERK signaling pathways (19). Based on these findings, we explored whether irisin may activate STAT3/AMPK/ERK signaling in mouse HT19-7 HN cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Western Blotting was performed as described previously (19). Measurement of signal intensity on nitrocellulose membranes after Western Blotting with various antibodies was performed using Image J processing and analysis software (http://rsbweb.nih.gov/ij/, August 25 th , 2011).…”
Section: Methodsmentioning
confidence: 99%
“…These anti-inflammatory effects might.be involved in preventing the neuronal cell death caused by CPS. AMP-activated protein kinase (AMPK) regulates signalling pathways related to cell survival and apoptosis and plays a role in increasing hippocampal neurogenesis [33] . It has been argued that AMPK activation directly inhibits β-amyloid accumulation in vitro [34,35] .…”
Section: Discussionmentioning
confidence: 99%